Price duration versus trading volume in high-frequency data for selected DAX companies - Christoph Mitterer; Henryk Gurgul; Robert Syrek (Managerial Economics)
The properties of the time series of durations between consecutive trades of a particular stock have been studied by many contributors in the literature of financial econometrics. Among them are highly prominent scientists like Engle (2000) and Gourieroux and Jasiak (2001). The importance of this topic, accompanied by the growing availability of (ultra-)high-frequency data, has prompted an increase of contributions in recent years. Intensive research based on high-frequency data has several financial motivations. First of all, it is linked with microstructure theory. Secondly, it contributes to the literature on stochastic time deformation. But the most important need for research on the dynamics of trade durations is the necessity to manage liquidity risk. The reason is that durations between the following trades are a widely accepted measures of market liquidity. In addition, their volatility reflects the liquidity risk.